Desain Produk Dan Stasiun Kerja Industri Kreatif Gelas Limbah Kayu dengan Metode QFD - Iwan Satriyo. N; Darwin Nahwan; Noneng Nurhayani; Mahyuddin Rahim; Adjie Bagaskara (Media Nusantara, 2021)
The Covid 19 pandemic has had an impact on the economy, such as factories in Cimanggung District, Sumedang Regency, laying off their employees. Lecturers and students try to solve this problem by building SMEs. This begins by analyzing the village’s potential in the form of mahogany waste and the potential of community human resources as former wood furniture workers. The method used in the design is Quality Function Deployment which can be interpreted as the implementation of achieving product quality which is judged by the level of customer satisfaction being pursued. So this method has an approach by involving consumers and stakeholders in every design stage. Based on the research results, this creative product design will be accepted by consumers if it meets the aspects of ergonomic design, durable and strong material, environmentally friendly, has attractive colors and designs as well as prices and uses are appropriate. Based on this research, a product prototype is formed. The size of mahogany glass products based on anthropometric data is divided into 3 size categories. Small size (S), medium size (M), and large size (L). Anthropometric data processed are work station design data and work desks/chairs. From the calculation and design, ergonomic work stations are produced, namely cutting, turning, assembly and finishing work stations.